Magnitude of Unnatural Deaths amongst Autopsies Over a Period of 4 Years at a Tertiary Centre Catering to Both Urban and Rural Population - Udaya Shankar B S; Shivakumar B C2; Sujatha P L; Tyagaraju M R (Institute of Medico-legal Publications Pvt Ltd, 2021)
Descriptive study of “Magnitude of Unnatural deaths amongst autopsies” was carried out at a tertiary carecentrecatering to urban and rural populationwith aims todetermine cause & manner of unnatural deathsandto estimate its magnitude according to area and sex.840 cases (81%) fulfilled criteria,male: female ratio was 2.28:1. In urban & rural areas;vulnerable age groupwas 21-30 years (35% &29%) followed by 31-40 years (23% &20%); most cases were hanging (49%&32%) followed by RTA (27% & 31%) & poisoning (10% & 19%).Suicides (60% & 55%) were more thanaccidents (35% & 42%) & homicides (5% & 3%). Hanging was more common in urban, whereas RTA &poisoning common in rural areas. More percentage females succumbed to hanging & poisoning whereasmore males to RTA, electrocution & fall from height. Males succumbed mostly during 6 am-12 pm (161)& 8 pm-6 am (157); whereas females succumbed mostly during 6 am-12 pm (74) & 69 cases each in 12-4pm & 4-8 pm.This study indicates need of strategies to curb unnatural deathsthrough health education& safety measures,counseling & treatment of depression; and better roads with signal boards.Unnatural;Cause; Manner of death;Urban;Rural